A cross-cultural comparison of where drivers choose to look when viewing driving scenes. (August 2021) - Miller, Karl A.; Chapman, Peter; Sheppard, Elizabeth
Highlights: The effect of culture on drivers' visual search was investigated. Drivers indicated where they would look across a series of roads. Malaysian drivers tended to look at more irrelevant information than UK drivers. Results suggest that drivers' visual search may differ across cultures. Abstract: A substantial proportion of road accidents occur as a result of drivers having poor or insufficient visual search strategies. However, the majority of research into drivers visual search comes from high income Western countries where roads are relatively safe, with less being known about the visual search of drivers from non-western, low and middle income countries with much higher crash rates. This is despite the fact that cross-cultural studies have shown differences in visual search outside of driving between Western and Eastern individuals. The current study aimed to see whether these differences were present in driving by asking UK and Malaysian drivers to select where they would look when viewing images of roads from the perspective of a driver. Results showed that all drivers selected a similar number of focal objects, however there was a difference in the type of background information drivers chose to attend to, with Malaysian drivers selecting more task irrelevant information at the expense of task relevant information. Results suggest that there are cultural differences in what drivers choose to attend to which may contribute to the increased crash rate amongst drivers from low and middle income countries.